Analisis Tingkat Pencemaran SO2 pada Udara Ambien Akibat Aktivitas Kendaraan Bermotor di Jalan A.H Nasution Kota Kendari - Mulyadin, Arwan; Ilham, Ilham; Rosdiana, Rosdiana (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
The air condition on our earth is getting worse day by day due to air pollution. Air pollution changes the composition (composition) of the atmosphere, where the amount and concentration of one or more pollutants endangers the health of living things, damages property, and reduces air comfort. The dense use of motorized vehicle activities in Kendari City is one of the factors that affect ambient air quality. This is what can be used as a reference in conducting this research using a field survey method for the number of vehicles and ambient air dampel testing for air quality in Kendari City with Sulfur Dioxide parameters. The results showed that the daily traffic density at the monitoring point on Jalan A.H Nasution, Kendari City, for motor vehicles was 8,046 units/day, cars were 3,237 units/day, and trucks were 213 units/day. Based on the results of laboratory tests, the concentration of SO2 at the measurement point on Jalan A.H Nasution, Kendari City, was 38.5 g/m3 in the morning, 61.7 g/m3 in the afternoon, and 53.5 g/m3 in the afternoon. Based on government regulation Number 22 of 2021 concerning the implementation and management of the environment, the sulfur dioxide concentration on the A.H Nasuton road, Kendari City, between morning, afternoon and evening is still below the quality standard threshold.